2013
DOI: 10.5114/pm.2013.33417
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections in the menopausal period: optimal management

Abstract: StreszczenieZakażenia układu moczowego są jednymi z najczęstszych chorób infekcyjnych u kobiet. Szczególnie często obserwuje się je w dwóch okresach życia: u młodych, aktywnych seksualnie kobiet oraz w okresie pomenopauzalnym. Istnieje wiele zmieniających się wraz z wiekiem przyczyn powodujących niepowikłane zapalenie pęche-rza moczowego. W okresie menopauzy takimi dobrze znanymi czynnikami są: zaleganie moczu w pęcherzu po mikcji, zmniejszony strumień moczu, nietrzymanie moczu, zaburzenia funkcji dna miednicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…14 often does not call for treatment. This finding is consistent with the study that was documented by Milart et al 17 They found that women who had gone through menopause did not require treatment for asymptomatic bacteriuria.…”
Section: Discussionsupporting
confidence: 93%
“…14 often does not call for treatment. This finding is consistent with the study that was documented by Milart et al 17 They found that women who had gone through menopause did not require treatment for asymptomatic bacteriuria.…”
Section: Discussionsupporting
confidence: 93%
“…In pre-menopausal women, sexual activities three or more times a week, the use of spermicides, new or multiple sexual partners and having suffered from UTI before age 15 are the main risk factors in UTI development and recurrence. In menopausal women, systemic hormonal therapy is not an effective prevention and usually asymptomatic bacteriuria during this period does not require treatment (Milart et al, 2013 ). In women after menopause, the risk increases mainly by low estrogen levels after-effects, which are often associated to vaginal atrophy (Arnold et al, 2016 ).…”
Section: Urinary Tract Infections (Utis)mentioning
confidence: 99%